Implementasi Program 3M Plus untuk Pemberantasan Sarang Nyamuk Aedes Aegypti di Gampong Dham Pulo, Aceh Besar - Pasyamei Rembune Kala; Quranayati Quranayati; Deski Nadya; Nazka Salsabila (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Dengue Hemorrhagic Fever (DHF) is dengue fever accompanied by liver enlargement and bleeding manifestations. Pemberantasan Sarang Nyamuk (PSN) remains the spearhead of breaking the chain of disease transmission (vector borne disease), in this case mosquitoes. PSN's understanding of the community plays a role in instilling 3M Plus behavior in the family maybe, which is used as the basis for their thinking and behavior. One of the programs developed is the 3M Plus program. The purpose of this activity is to provide education on PSN with the 3M Plus Program and also as a prevention effort. The methods used are contextual and participatory approaches, with extension demonstrations, training, demonstrations/hands-on practice. The results obtained are that the public is increasingly understanding Mosquito Nest Eradication and the 3M Plus program, starting from the definition, impact and prevention methods of Mosquito Nest Eradication with the 3M Plus program. It is recommended that there is a need for regular monitoring of 3M Plus, and intensive coaching so that this activity is sustainable so that there are no more places for Aedes Aegypti mosquitoes to breed can continue to be obtained as an indicator of the presence of larvae in residential environments and public places.